Loneliness and Social Functioning in Adolescent Peer Victimization - Almeida, Telma Sousa; Ribeiro, Olivia; Freitas, Miguel; Rubin, Kenneth H.; Santos, António J. (Frontiers in Psychology, 2021)
Interpersonal adversity such as peer victimization has been shown to have complex associations with other socio-emotional difficulties, particularly during adolescence. We used a multidimensional peer-nomination measure on a sample of 440 11- to 17-year-old Portuguese youths to identify three groups, classified by peers as 1) victimized adolescents who showed anxious-withdrawn behaviors in the context of the peer group, 2) victimized adolescents who did not exhibit anxious-withdrawn behaviors, and 3) non-victimized adolescents. We compared these groups on their peer-reported social functioning and on their self-reported feelings of social and emotional loneliness (with peers and family). Anxiously-withdrawn victims were viewed by peers as more excluded, less aggressive, less prosocial and less popular than non-withdrawn victims and non-victims. Non-anxiously-withdrawn victims were considered more excluded than non-victims, and more aggressive than both anxiously-withdrawn victims and non-victims. Finally, anxiously-withdrawn victims reported feeling less integrated and intimate with their peers than non-withdrawn victims and non-victims, which is indicative of greater feelings of social and emotional loneliness at school. Youths in the current study did not report feeling lonely in their family environment. Our findings thus provide further evidence that victimized youths constitute a heterogeneous group, which differ in the way they behave toward their peers and experience loneliness.